THE SELF-ACTUALIZATION OF SARA CREWE IN A LITTLE PRINCESS NOVEL BY FRANCES HODGSON BURNETT - Kartina, Ema; Natsir, M.; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
ABSTRACT The research was conducted to analyze the character of Sara Crewe in A Little Princess novel by Frances Hodgson Burnett. A Little Princess was chosen as the novel in this research because the main character, Sara, was described as a brave and tough young girl who could deal with the difficulties in her lives. The objective of this research was to find out the characteristics of self-actualizing person and the imperfection of self-actualizing person in Sara’s character by Sara’s feeling, behavior, thought and all the factors and events. This research was under a qualitative research and employed literary and psychology approach to get deeper understanding about the main character's characterization. The source of the data was taken from the novel A Little Princess by Frances Hodgson Burnett. Reading the novel carefully and deeply then separating the data by signing and making some notes were the steps in collecting the data. This research used theory of Self-Actualization by Maslow to explain the characteristics of self-actualizing person and the imperfection of self-actualizing in Sara’s character. The result of this research showed that from fifteen characteristics of self-actualizing person by Maslow, Sara has fourteen characteristics in her character while Sara also has the imperfection's characteristics such as stubborn, unexpected ruthless and forget the social politeness. Therefore, the researcher found the characterization of Sara through the aspect of psychological and moral, the narration and the conversations in the story. ABSTRACT Penelitian ini dilakukan untuk menganalisa karakter Sara Crewe di novel A Little Princess oleh Frances Hudgson Burnett. Novel A Little Princess dipilih di dalam penelitian ini karena Sara sebagai karakter utama menunjukkan sikap berani dan kuat sebagai gadis muda yang dapat menghadapi kesulitan-kesulitan di hidupnya. Tujuan penelitian adalah untuk mengetahui karakteristik dari keaktualisasian diri sesorang dan ketidaksempurnaan dari sesorang yang mengaktualisasi diri yang dilihat dari karakter Sara berdasarkan perasaannya, perilakunya, pemikirannya dan segala factor-faktor dan kejadian-kejadian yang berhubungan dengan analisa tersebut. Penelitian ini adalah penelitian kwalitatifyang menggunakan pendekatan kesusastraan dan psikologi agar mengerti lebih dalam tentang perwatakan dari satu karakter. Sumber data diambil dari novel A Little Princess oleh Frances Hodgson Burnett. Membaca novel dengan perlahan dan mendalam lalu memisahkan data yang bersangkutan dengan menandai dan membuat beberapa catatan merupakan langkah-langkah dalam mengumpulkan data. Penelitian ini menggunakan teori keaktualisasian diri dari Maslow untuk mejelaskan karakteristik-karakteristik seseorang yang mengaktualisasi diri serta ketidaksempurnan dalam mengaktualisasi diri yang dilihat berdasarkan karakter Sara. Hasil penelitian menunjukkan bahwa dari 15 karateristik seseorang dalam mengaktualisasi diri oleh Maslow, ada 14 karakteristik yang terlihat di karakter Sara, sementara Sara juga memiliki karakter dari ketidaksempurnaan dari mengaktualisasi diri yaitu keras kepala, kekejaman yang tak disangka, dan melupakan kesopanan sosial. Bagaimanapun, peneliti menemukan perwatakan Sara tersebut melalui aspek psokologis dan moral, pengisahan dan perbincangan yang ada di dalam novel.